THE COMPARISON OF RESISTANCE OF KCL POLYMER POLYAMINE'S MUD TO HIGH TEMPERATURE - kusrini, Desi kusrini; Andi Vira (PT. Jurnal Center Indonesia Publisher, 2026)
X is a company engaged in non-construction oil & gas services, namely water base mud (polyamine based) management services, supply of chemical materials, laboratory equipment, and drilling fluid engineers for oil and gas drilling. problems encountered when drilling through formations containing reactive clay and shale which can cause swelling clay problems and formation damage. This problem can be overcome with a high performance water based mud (HPWBM) mud system which has a super shale inhibition (polyamine) component. Mud which is formulated with the concept of total inhibitor, has inhibitory properties that can stabilize mineral clay and shale. The of this final assignment are to identify and study the high performance water base mud (HPWBM) mud system, then to know the ratio of good polyamines to be used in the KCL polymer polyamine mud formulation, then to look for the value of the physical properties of the KCL polymer polyamine mud formulation. to meet the oil company spec. This test begins with testing the mud properties of the KCl polymer polyamine mud sample from PT. Mitra Mandiri Saktitama before being exposed to Temperature and after being exposed to Temperature. Then analyze the changes in the value of the mud properties that have been made and the specifications of their physical properties, so that they can look for changes in the values of the mud properties of KCl polymer polyamine mud that fall within the specified range of mud properties. This test is carried out under the conditions of a room temperature of 78-300°F.